Flavor Biochemistry of Fermented Alcoholic Beverages - de Castilhos, Maurício B. M.; de Queiroga, Ana P. G.; Sabino, Lia L.; dos Santos Júnior, Jorge R. [UNESP]; Santiago-Urbina, Jorge A.; Nolasco-Cancino, Hipócrates; Ruíz-Terán, Francisco; Del Bianchi, Vanildo L. [UNESP] (Wiley, 2021)
The flavor is one of the sensory attributes that panelists assess and its complexity brings several discussions regarding the definition of its concept. Some authors describe the flavor as a sum of perceptions resulting from the stimulation of the senses by the food/beverage in the digestive and respiratory tracts; other authors define flavor as a combination of taste and mouthfeel. There is a tendency to consider the relevance of the relationship between the flavor and the chemical food/beverage matrix. Acids, alcohols, volatile compounds, and other chemical substances are responsible for distinctive sensations in the mouth promoting different tastes and mouthfeel. In addition, the synthesis path of the chemical substances that respond to flavor compounds is based on relevant biochemical phenomena. In this context, alcoholic fermentation is considered one of the most essential biochemical reactions providing the formation of a set of volatile compounds responsible for influencing the flavor. Wine and mezcal are examples of alcoholic beverages that present several chemical compounds responsible for their complex flavor due to the several biochemical reactions that occur during their production. Esters, higher alcohols, carbonyl compounds, and oak flavors such as lactones, furanic compounds, and methoxyphenols are responsible for providing the complex flavor that differentiates the wines. Other factors such as the intrinsic features of the grape cultivar and the grape vintage also influence the wine flavor. The most relevant biochemical pathway that produces the chemical compounds that respond to wine flavor is the synthesis of different enzymes produced by the different yeasts responsible for alcoholic fermentation. Also, mezcal is produced by different species of maguey and its cooking is the first step that generates caramel and smoky notes related to furans, alcohols, aldehydes, ketones, phenols, and terpenes. The chemical composition of the mezcal depends on the maguey species, age, the chemical composition of the maguey, and the practice of each producer. The use of autochthonous yeasts during alcoholic fermentation and the conditions used for the biochemical reaction respond to the mezcal flavor differences. In summary, biochemical reactions have substantial importance for the flavor complexity of wine and mezcal since the different flavor nuances are explained by the different chemical composition of the grape and maguey, respectively, the conditions used during the process, and the yeasts involved in the alcoholic fermentation. The study of biochemical pathways will be helpful for wineries and mezcal producers to elucidate the mechanism of the reactions involving the synthesis of specific chemical compounds and their respective flavor notes, producing a safe beverage with quality and high acceptance.
Keywords: alcoholic beverage; alcoholic fermentation; biochemical reaction; flavor; flavor biochemistry; Mezcal; wine